ESTABLISHMENT AND CALCULATION OF THE AMOUNT OF COMPENSATION FOR ENVIRONMENTAL DAMAGE FROM A STATIONARY SOURCE OF EMISSIONS OF POLLUTANTS INTO THE ATMOSPHERIC AIR - Pazniak, Sergei S. (Journal of the Belarusian State University. Ecology, 2026)
In the course of the research, methodical aspects related to the establishment of signs of negative anthropogenic impact of emissions of pollutants into the atmospheric air, as well as with the features of calculating the amount of compensation for damage caused to the environment from a stationary source of emissions of pollutants into the atmospheric air were determined. A step-by-step algorithm for expert analysis of air pollutant emissions from stationary sources is described. This algorithm allows for a more accurate classification of signs of negative anthropogenic impact on environmental objects (establishing the fact of harm), the correct interpretation of the obtained research results, the presentation of the results of the damage cost assessment, and the formulation of answers to the expert’s questions. An example of calculating the amount of damage caused to the environment is considered, taking into account the category of the object impacting the air and the hazard class of the substance released or resulting from the release of the pollutant into the atmosphere